Reinforcing loose foundation stones in trait-based plant ecology - Shipley, Bill; De Bello, Francesco; Cornelissen, J Hans C; Laliberté, Etienne; Laughlin, Daniel C; Reich, Peter B (Oecologia, 2016)
The promise of "trait-based" plant ecology is one of generalized prediction across organizational and spatial scales, independent of taxonomy. This promise is a major reason for the increased popularity of this approach. Here, we argue that some important foundational assumptions of trait-based ecology have not received sufficient empirical evaluation. We identify three such assumptions and, where possible, suggest methods of improvement: (i) traits are functional to the degree that they determine individual fitness, (ii) intraspecific variation in functional traits can be largely ignored, and (iii) functional traits show general predictive relationships to measurable environmental gradients.
Keywords: Environment; rostliny; Plants; druhová specificita; fenotyp; Comparative ecology; životní prostředí; Ecology; Phenotype; Functional ecology; ekologie; Environmental gradients; Species Specificity; Intraspecific variation